2013
DOI: 10.1007/s11250-013-0470-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of month of breeding on reproductive efficiency of Holstein cows and heifers inseminated with sex-sorted or conventional semen in a hot environment

Abstract: The main objective of this study was to assess the effect of month of breeding on reproduction performance of Holstein heifers and cows inseminated with sex-sorted or conventional semen in a hot environment. Pregnancy per artificial insemination (P/AI; 64,666 services over an 8-year period) both in heifers (n = 22,313) and cows (n = 42,353) from a large dairy herd in northern Mexico (26°N) were evaluated with the GENMOD procedure of SAS, with respect to month of AI. Overall, P/AI with sex-sorted semen was grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
2
9
0
4
Order By: Relevance
“…The effect of insemination year and the breeding sire beside the sperm type were significant in the study conducted by Cerchiaro et al (2007). Mellado et al (2014) reported that the difference in the conception rate among sexed and conventional semen is related to the month of insemination. Lower conception rate of sexed versus conventional semen is highly related to both decreased numbers of sperm per doses of semen in addition to the damage occurred to spermatozoa during the semen sorting process (Bodmer et al 2005;Garner & Seidel Jr 2008;DeJarnette et al 2011).…”
Section: Conception Rate and The Number Of Services Per Conceptionmentioning
confidence: 98%
“…The effect of insemination year and the breeding sire beside the sperm type were significant in the study conducted by Cerchiaro et al (2007). Mellado et al (2014) reported that the difference in the conception rate among sexed and conventional semen is related to the month of insemination. Lower conception rate of sexed versus conventional semen is highly related to both decreased numbers of sperm per doses of semen in addition to the damage occurred to spermatozoa during the semen sorting process (Bodmer et al 2005;Garner & Seidel Jr 2008;DeJarnette et al 2011).…”
Section: Conception Rate and The Number Of Services Per Conceptionmentioning
confidence: 98%
“…Similarly, Donovan et al (2003) reported that the pregnancy rate of sexed AI in heifers in summer (33%) was only approximately half of that in winter (64%). The pregnancy rates in dairy cows are generally lower than those in heifers, but show the same trend in that summer is the worst season: 16% in summer and 21% in winter in a recent study (Mellado et al 2014). …”
Section: Introductionmentioning
confidence: 68%
“…The pregnancy rate had no significant effect on heifers inseminated with sex-sorted semen in the cool and hot seasons. In the annual research of Mellado et al (2014), the pregnancy rate of heifers inseminated using sex-sorted semen was significantly higher than that of cows; there was no significant effect of insemination using sex-sorted semen on the pregnancy rate of heifers in the cool season and the hot season. This result is similar to that of our experiment; there was no significant effect of insemination using sex-sorted semen on the pregnancy rate of heifers in the cool season or the hot season in subtropical regions.…”
Section: Discussionmentioning
confidence: 91%
“…W lipcu wartości te były porównywalne (44). Wydaje się, że w przypadku nasienia sortowanego promowane są embrionalne mechanizmy termoprotekcyjne, co łagodzi supresję płodności w warunkach klimatu gorącego (45).…”
unclassified
“…Z kolei odsetek ciąż uzyskiwany po transferze zarodków produkowanych in vitro po inseminacji nasieniem seksowanym, konwencjonalnym lub produkowanych in vivo wynosił, odpowiednio, 40,9%, 41,9% i 53,1% (69). Odsetek ciąż wynosił 46,1% i 32,5%, jeśli przenoszono zarodki wyprodukowane w warunkach laboratoryjnych, posiadające obustronne pochodzenie po bydle gyr lub rasy holsztyńsko-fryzyjskiej (45). Zarodki o mieszanym pochodzeniu zapewniały wskaźnik zacieleń na poziomie 38,9-40,3%.…”
unclassified